Sifat fisikokimia dan organoleptik chiffon cake gluten free berbahan tepung uwi putih (Dioscorea alata) dan tepung mocaf: Physicochemical and organoleptic properties of gluten free chiffon cake made from white yam flour (Dioscorea alata) and mocaf flour - Jehandu, Maria Yuliana Permatasari; Handarini, Kejora; Hartati, Fadjar Kurnia (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2025)
Chiffon cake is a popular cake in the world and has the advantage of a soft, cotton-like texture. The utilization of white yam flour and mocaf flour needs to be studied to produce a texture similar to the texture of chiffon cake made from wheat flour. White yam flour and mocaf flour are local food sources that are useful in the context of efforts to substitute the use of wheat flour in Indonesia. The purpose of this study was to determine the best treatment of white yam flour (Dioscorea alata) concentration with mocaf flour on the physicochemical and organoleptic properties of gluten free chiffon cake. This study used a laboratory experimental method using a one-factor Completely Randomized Design (CRD) with 4 treatment levels, namely the ratio of the concentration of white yam flour and mocaf flour consisting of treatment P1 (100%: 0%), P2 (85%: 15%), P3 (70%: 30%), P4 (55%: 45%). This research was conducted 3 times. The test parameters carried out were physical properties, namely the rise of chiffon cake. Chemical properties consist of water content, fat content, crude fiber content and sugar content. Organoleptic properties consist of color, taste, aroma and texture. The results showed that the use of 100% white yam flour gave the best results on the physical, chemical, and organoleptic characteristics of gluten free chiffon cake. The use of mocaf flour increased sugar content and fat content while reducing physical and sensory properties. This shows that white yam flour